SIRT6 as a key event linking P53 and NRF2 counteracts APAP-induced hepatotoxicity through inhibiting oxidative stress and promoting hepatocyte proliferation - Yanying Zhou; Xiaomei Fan; Tingying Jiao; Wenzhou Li; Panpan Chen; Yiming Jiang; Jiahong Sun; Yixin Chen; Pan Chen; Lihuan Guan; Yajie Wen; Min Huang; et al. (Elsevier, 2021)
Acetaminophen (APAP) overdose is the leading cause of drug-induced liver injury, and its prognosis depends on the balance between hepatocyte death and regeneration. Sirtuin 6 (SIRT6) has been reported to protect against oxidative stress-associated DNA damage. But whether SIRT6 regulates APAP-induced hepatotoxicity remains unclear. In this study, the protein expression of nuclear and total SIRT6 was up-regulated in mice liver at 6 and 48 h following APAP treatment, respectively. Sirt6 knockdown in AML12 cells aggravated APAP-induced hepatocyte death and oxidative stress, inhibited cell viability and proliferation, and downregulated CCNA1, CCND1 and CKD4 protein levels. Sirt6 knockdown significantly prevented APAP-induced NRF2 activation, reduced the transcriptional activities of GSTμ and NQO1 and the mRNA levels of Nrf2, Ho-1, Gstα and Gstμ. Furthermore, SIRT6 showed potential protein interaction with NRF2 as evidenced by co-immunoprecipitation (Co-IP) assay. Additionally, the protective effect of P53 against APAP-induced hepatocytes injury was Sirt6-dependent. The Sirt6 mRNA was significantly down-regulated in P53−/− mice. P53 activated the transcriptional activity of SIRT6 and exerted interaction with SIRT6. Our results demonstrate that SIRT6 protects against APAP hepatotoxicity through alleviating oxidative stress and promoting hepatocyte proliferation, and provide new insights in the function of SIRT6 as a crucial docking molecule linking P53 and NRF2.